The function of CD36 in Mycobacterium tuberculosis infection - Wang, Jianjun; Cao, Hui; Yang, Hongwei; Wang, Nan; Weng, Yiwei; Luo, Hao (Frontiers in Immunology, 2024)
CD36 is a scavenger receptor that has been reported to function as a signaling receptor that responds to pathogen-associated molecular patterns (PAMPs) and damageassociated molecular patterns (DAMPs) and could integrate metabolic pathways and cell signaling through its dual functions. Thereby influencing activation to regulate the immune response and immune cell differentiation. Recent studies have revealed that CD36 plays critical roles in the process of lipid metabolism, inflammatory response and immune process caused by Mycobacterium tuberculosis infection. This review will comprehensively investigate CD36's functions in lipid uptake and processing, inflammatory response, immune response and therapeutic targets and biomarkers in the infection process of M. tuberculosis. The study also raised outstanding issues in this field to designate future directions.